Dose of Protamine for Heparin Reversal in CABG Surgery - Syed Ali Raza Ali Shah; Syeda Sarah Naqvi; Syed Muzaffar Hasan Kirmani; Syed Aqeel Hussain; Imran Bashir Malik; Muhammad Umar Farooq (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the dose of Protamine required for reversal of Heparin effect in Coronary Artery Bypass Grafting (CABG).